Analisis Gaya Bahasa Dalam Cerpen Yang Berjudul “Banun” Karya Damhuri Muhammad - Rizki Putri Yunisa Khairani; Tiara Putri; Edi Syahputra (Universitas Dehasen Bengkulu, 2022)
This study aims to discuss and determine the style of language in the short story by Damhuri Muhammad entitled